Respostas

2013-08-27T19:13:40-03:00
F(-3)=3(-3)-2                     f(-2)=3(-2)-2                 f(-1)=3(-1)-2                f(0)=3.0-2
f(-3)=-9-2                         f(-2)=-6-2                      f(-1)=-3-2                    f(-0)=-2
f(-3)=-11                          f(-2)=-8                          f(-1)=-5

f(1)=3.1.-2                       f(2)=3.2-2                       f(3)=3.3-2
f(1)=3-2                           f(2)=6-2                          f(3)=9-2
f(1)=1                              f(2)=4                             f(3)=7